Analisis faktor-faktor yang mempengaruhi Kinerja pegawai pada dinas kesehatan Kabupaten kutai timur - Meita Sondang Rizki (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2016)
The study tries to identify to what extent incentive, competence, motivation, discipline, work environment, social security, nutrition and health of staff   Health Department, it will also identify which factors give the most impact toward staff performance.       This research excepted to benefit to all side, especially for institution head to dig elements that increasing performance of staff   Health Department  in Sangatta. Analysis model used to prove hypothesis is model analysis multiple linier regression that be analysed with using statistics computer program package, that is SPSS v. 14.0 for Windows. Responden that becoming objective this research  are counted 75 of staff  Health Department. Result of statistics analysis show that coefficient of the free variables regression, that is involvement  factor in incentive (X1) =  0,164, competence (X2) = 0,178, motivation (X3) = 0,148, discipline (X4) = 0,048, work environment (X5) = 0,287,  social security  (X6) = 0,176, nutrition and health  (X7) = 0,130, and constanta equal  to 0,366. Equation  of multiple linier regression is : Y = 0,366 + 0,164 X1 + 0,178 X2 + 0,148 X3 + 0,048 X4 + 0,287 X5 +  0,176 X6 + 0,130 X7 Conclusion that receive that level of influence explained by incentive, competence, motivation, discipline, work environment, social security, nutrition and health as independent variable impact toward performance of staff  Health Department equal to correlation  coefficient (R), that is 0,869  and level of depended  performance to seventh of  free variables above is equal to determination  coefficient value (R2) that is 0,755 or 75,5 %.  Result of analysis F – test  indicate that all free variables by together have significant influence toward performance of staff Health Department.  By parsial, variable incentive, competence, motivation, work environment, social security, nutrition and health  have  significant  influence to performance of staff  Health Department. Only one variable is discipline have no significant.  Variabel independent  have dominant influence to performance of staff   Health Department is work environment (X5).